Cryptococcal meningitis in non-human immunodeficiency virus patients: A case series - Mohanapriya, M; Kumar, E Senthil; Vijayakumar, A; Rajkumar, R (Indian Journal of Case Reports, 2024)
Cryptococcosis is a fungal infection caused by encapsulated yeast in the genus Cryptococcus. It is mostly observed in immunocompromised, organ transplant, and human immunodeficiency virus (HIV) positive patients, but it is also seen in non-HIV and immunocompetent patients. The majority of the cases have been reported in patients suffering from cryptococcal meningitis in HIV/acquired immunodeficiency syndrome. In this study, we reported a case series of three cases of cryptococcal meningitis in non-HIV patients. These cases were suspected and diagnosed according to their underlying immune status and clinical presentations.